1982
DOI: 10.3109/00016348209156958
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Uterine Arteriovenous Fistula

Abstract: A case of a uterine arteriovenous aneurysm in a 20-year-old woman is described. The patients's main symptom was copious uterine bleeding. The diagnostic difficulties are described and the importance of arteriography is emphasized. The aneurysm was occluded at laparotomy by introducing gel-foam into the uterine artery. The patient subsequently became pregnant and after an uneventful pregnancy was delivered of a healthy child. Thus, this type of conservative treatment seems to offer a possible means of avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…Duplex ultrasound 1 day later (f) revealed normalization of the uterine vasculature effective and less invasive than surgery, not only for the treatment of AUVM, but also for primary and secondary postpartum hemorrhage [13][14][15][16]. Transcatheter embolization of uterine arteries in the treatment of UVM was first described by Forssman et al [17], and several other case reports and small series showed a very high technical and clinical success rate. Badawy et al [18] reviewed all 25 cases published between 1982 and 1999 and found a success rate after one to two embolization procedures of 96% and a complication rate of 4%.…”
Section: Discussionmentioning
confidence: 96%
“…Duplex ultrasound 1 day later (f) revealed normalization of the uterine vasculature effective and less invasive than surgery, not only for the treatment of AUVM, but also for primary and secondary postpartum hemorrhage [13][14][15][16]. Transcatheter embolization of uterine arteries in the treatment of UVM was first described by Forssman et al [17], and several other case reports and small series showed a very high technical and clinical success rate. Badawy et al [18] reviewed all 25 cases published between 1982 and 1999 and found a success rate after one to two embolization procedures of 96% and a complication rate of 4%.…”
Section: Discussionmentioning
confidence: 96%
“…Procedimento conservador que melhor resultado tem alcançado é a embolização da artéria uterina 28 . A embolização da artéria uterina, cuja téc-nica está cristalizada 9,29,30 , representa alternativa à histerectomia, sendo boa opção para preservar a função reprodutiva nas pacientes acometidas por MAVU.…”
Section: Resultsunclassified
“…Embolotherapy has subsequently been used to control hemorrhage or blunt the clinical consequences of arteriovenous (AV) malformations occurring in several anatomic sites [22,23] and for cervical pregnancies [24][25][26][27]. Recently, this technique has been adopted to treat bleeding uterine leiomyomas (uterine fibroids) [28,29].…”
Section: Discussionmentioning
confidence: 99%